1999
DOI: 10.1024/0300-9831.69.2.127
|View full text |Cite
|
Sign up to set email alerts
|

The Age at which Meat is First Included in the Diet Affects the Incidence of Iron Deficiency and Ferropenic Anaemia in a Group of Pre-school Children from Madrid

Abstract: A study was made into the effect of the age at which meat was first included in the diet on a series of haematological parameters and biochemical indicators of iron status in 94 pre-school children (aged 2-6 years) from Madrid (Spain). Those children who first took meat during their eighth month of life or earlier (Group A) showed better iron status that did those who were introduced to meat later (Group B). Significant differences were found in hemoglobin levels (P < 0.01), mean corpuscular haemoglobin (MCH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Moreover, cow's milk is rich in calcium and casein, both known to inhibit iron absorption [85]. Other studies showed that late weaning, and particularly the late introduction of iron-rich meat, is an important predictor of iron deficiency in children older than 1 year [86,87]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cow's milk is rich in calcium and casein, both known to inhibit iron absorption [85]. Other studies showed that late weaning, and particularly the late introduction of iron-rich meat, is an important predictor of iron deficiency in children older than 1 year [86,87]. …”
Section: Discussionmentioning
confidence: 99%
“…The question of whether red meat is superior to poultry and/or fish in enhancing iron status is less well researched. Most observational studies have found a positive association between iron status (Doyle et al , 1999; Donovan and Gibson, 1995; Ortega et al , 1998; Requejo et al , 1999; Thane et al , 2000; Thane and Bates, 2001; Hua et al , 2001; Milman et al , 2003; Thane et al , 2003) and meat consumption and a few have found a stronger and/or a specific association with red meat (Worthington‐Roberts et al , 1988; Gibson and Ashwell, 2003; Wolmarans et al , 2003). Our findings of a non‐significant association with poultry are tentative and require further exploration, but may be biologically plausible given the lower iron and haem iron content of poultry compared with beef, lamb or pork.…”
Section: Discussionmentioning
confidence: 99%
“…This figure grossly underestimates the value of meat for influencing iron status. A Spanish study showed that children who first ate meat before eight months of age showed a better iron status than those who were introduced to meat later than eight months (Requejo et al, 1999). Low iron intakes and status are common among certain subgroups of the population; toddlers (Gregory et al, 1995;Edmond et al, 1996), adolescents (Nelson et al, 1993Nelson, 1996), pregnant women (Allen, 1997 and the elderly (Finch et al, 1998).…”
Section: Iron In Meatmentioning
confidence: 99%